Depression In Adolescent Patients with Obesity - Rabbani, M. Iqbal Ali (Scientia Psychiatrica, 2023)
Depression and obesity are two common illnesses with serious public health consequences that frequently co-occur in people. The link between both conditions is bidirectional: having one raises your chances of getting the other. Obesity and depression are both prevalent during adolescence, and obesity may be a trigger for adolescent depression.